Systematic verification of bladder cancer-associated tissue protein biomarker candidates in clinical urine specimens - Tsai, Cheng-Han (Oncotarget, 2018)
Bladder cancer biomarkers currently approved by the Food and Drug Administration are insufficiently reliable for use in non-invasive clinical diagnosis. Verification/validation of numerous biomarker candidates for BC detection is a crucial bottleneck for novel biomarker development. A multiplexed liquid chromatography multiple-reaction-monitoring mass spectrometry assay of 122 proteins, including 118 up-regulated tissue proteins, two known bladder cancer biomarkers and two housekeeping gene products, was successfully established for protein quantification in clinical urine specimens. Quantification of 122 proteins was performed on a large cohort of urine specimens representing a variety of conditions, including 142 hernia, 126 bladder cancer, 67 hematuria, and 59 urinary tract infection samples. ANXA3 (annexin A3) and HSPE1 (heat shock protein family E member 1), which showed the highest detection frequency in bladder cancer samples, were selected for further validation. Western blotting showed that urinary ANXA3 and HSPE1 protein levels were higher in bladder cancer samples than in hernia samples, and enzyme-linked immunosorbent assays confirmed a higher urinary concentration of HSPE1 in bladder cancer than in hernia, hematuria and urinary tract infection. Immunohistochemical analyses showed significantly elevated levels of HSPE1 in tumor cells compared with non-cancerous bladder epithelial cells, suggesting that HSPE1 could be a useful tumor tissue marker for the specific detection of bladder cancer. Collectively, our findings provide valuable information for future validation of potential biomarkers for bladder cancer diagnosis.